PENAKSIRAN POPULASI TAPIR ASIA (Tapirus indicus) DI SUAKA MARGASATWA RIMBANG BALING DENGAN BANTUAN KAMERA JEBAK - Nuri Asmita; Ahmad Muhammad; Sunarto ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The island of Sumatra harbors a few large ungulates, including the endangered Asian tapir, Tapirus indicus, whose population is believed dwindling due to habitat loss and fragmentations. Recent surveys indicated that the species occurs in a wide range of habitats which are strongly affiliated to natural forests. In Riau Province, Rimbang-Baling Wildlife Reserve is one of the remaining pockets of tapir population. We have conducted a preliminary assessment of tapir population in this reserve using camera traps. We operated 20 camera-traps in 20 systematically grids. From 1,710 effective trap nights, 304 images of tapir with 71 independent images were obtained, which were identified as 14 individuals. Based on the best models developed in DENSITY Program Version 4.4, we estimated that there were 7.60 ± 2.40 (D±SE)tapir individuals/100 km2 in the surveyed area. Our study provided the first density estimate of this endangered speciesin Sumatra using Spatial Explicit Capture-Recapture method. The findings indicate that Rimbang Baling is an important area that should be protected more effectively if the Asian tapirs want to be conserved for the long term.